Association between Depressed Mood and Youth Condom/Contraceptive Nonuse: A Systematic Review of Literature. (1st February 2018) - Ghobadzadeh, Maryam; Moore, Derek
ABSTRACT: Purpose : The purpose of this review article was to determine whether an association exists between depressed mood and contraceptive/condom nonuse among adolescents and young adults. Methods : CINAHL, Google Scholar, the ProQuest Digital Dissertations and PubMed databases were searched from 1990 through 2016. Longitudinal and cross-sectional studies focusing on the associations between depressed mood and sexual risk behavior of youths or adolescents, aged 12–26 years, were eligible. Study quality was assessed by the criteria for methodology, measurements, description of attrition rates/follow up, sampling methods, and controlling for potential confounders. Results : Twenty seven eligible studies were found, including 12 cross-sectional studies, 11 prospective observational studies, and 4 longitudinal randomized interventions. There were a number of potential methodological problems in many of the research studies. Methodological limitations include use of purely cross-sectional research designs and reliance on self-report measures and the long time interval between the baseline and the follow-up data. Conclusions : There is fair evidence of an association of depressed mood with contraceptive nonuse. Further specific analyses need to be conducted on this topic. Additional research using true prospective design and improved reporting on the measure of both exposure and outcome are also needed to provide more reliable findings and facilitate improved understanding of the association between depressed mood and sexual risk behavior.